Non-standard workers and the self-employed in the EU: Social protection during the Covid-19 pandemic - Slavina Spasova; Dalila Ghailani; Sebastiano Sabato; Stéphanie Coster; Boris Fronteddu; Bart Vanhercke (European Trade Union Institute (ETUI), 2021)
The lockdown and other restrictive measures introduced during the Covid-19 pandemic and the ensuing economic recession have had a strong impact on labour markets worldwide. As far as the European Union (EU) is concerned, the accelerated fall in total employment was the 'sharpest decline ever observed over two successive quarters since 1995'. Unemployment, however, decreased moderately over 2020, although to differing extents in individual Member States and at different paces during the various lockdown phases. This exceptional and unpredictable context puts the pivotal role of social protection squarely in the spotlight, reminding policymakers and citizens of the essential role of strong social security to cushion against potential disastrous social impacts and job destruction. Various job retention schemes have played an important role as automatic stabilisers to preserve millions of jobs. The purpose of the present study is to map key social protection measures taken during the pandemic from the perspective of fragmentation of labour market statuses, notably by focusing on non-standard workers and the self-employed as well as taking into account the gender dimension of these social protection measures. The analysis focuses on the 27 EU Member States, covering the period of the first wave of the pandemic: from the beginning of the lockdown measures (for most countries at the beginning of March 2020) until 31 December 2020. The remainder of the publication is structured as follows. Section 1 discusses the relevance and research design and explains the broader project of which this analysis is part. Section 2 describes the measures taken regarding unemployment benefits during the pandemic. Section 3 focuses on sick pay and sickness benefits. Section 4 discusses the special Covid-19 parental leave arrangements. The conclusions highlight the main trends in the measures taken during the first wave of the pandemic as well as their relevance for non-standard workers and the selfemployed. This mapping report is the first deliverable of a larger study which the European Social Observatory is conducting on behalf of the European Trade Union Institute (ETUI).
Keywords: 330; atypical employment; self-employed; coronavirus; Social Security; wage replacement benefits; job security; EU countries; Atypische Beschäftigung; Selbstständige; Coronavirus; Soziale Sicherheit; Lohnersatzleistungen; Beschäftigungssicherung; Vergleich; EU-Staaten